Dual Etiologic Back Pain in Pregnancy: A Case Report with Lumbar Disc Herniation and Transient Osteoporosis of the Bilateral Hip - Aynur Aydoğan İzol; Belgin Erhan; Neriman Rençber (Galenos Yayinevi, 2017)
Low back pain in pregnancy is a common complaint. It has been reported that the pregnancy is an independent risk factor for lomber disc herniation and may worsen the existing herniation. Transient osteoporosis of the hip (TOH), is a rare, self-limiting and gestational disease of unknown cause. In this article, we report a case of acute lomber disc hernia and later bilateral temporal osteoporosis of the hip that was treated with conservative methods during the same gestational period. With this pathologic case it is emphasized that, two pathological phenomenon can be seen in the same patient at the same time. It should be kept in mind TOH and radiculopathy should be considered in the differential diagnosis in pregnant patients who complains back and hip pain.